(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
A study was conducted with aim of determining toxicity effects of Piper guineense and chlorpyrifos powders on adult mortality of Callosobruchus subinnotatus, progeny emergence (F1), damage and weight loss, germination of Bambara nuts. Study was carried out at Botany laboratory, Gombe State University, Gombe State, Nigeria. P. guineense and chlorpyrifos were mixed at 0.0g and 0.8g concentration with 20g Bambara nuts inside 1000ml plastic containers. Experiment was conducted in randomized complete block design in three replicates. Ten pairs of adult C. subinnotatus unsexed were introduced into treatments nuts and stored for 7days. Bruchid mortality, progeny emergence, nut damage and weight loss, and germination were assessed. Data obtained were subjected to analyses of variance, significant differences of treatment mean were separated using New Duncan’s multiple range test at 5% probability level. Piper guineense and chlorpyrifos powders had comparable toxicity effects, causing 100% C. subinnotatus adult mortality between 5-7 days of treatment. P. guineense and chlorpyrifos powders proved effective as lower C. subinnotatus progeny emergence was observed compared with control. Progeny emergence under control was 93.42% and 100% higher than nuts treated with P. guineense and chlorpyrifos, respectively. P. guineense and chlorpyrifos did not cause significant reduction in seed germination. Study recommends P. guineense is a reliable organic material that could offer protection to Bambara nuts against C. subinnotatus